Enhancing patient self-management after a first stroke: An application of the wearable devices and the health management platform. Issue 1 (January 2023) - Wu, Jia-Min; Chen, Hsin-Shui; Chen, Hsin-Han; Cheng, Bor-Wen; Huang, Chiu-Wen; Chung, Ming-Hung
Abstract: Background: Post-stroke disability restricts a patient's physical activity, affects the patient's quality of life, and leads to higher medical costs. Therefore, it is essential to promote patients' continuous exercise during this period of recovery. Objective: This study aimed to verify the effectiveness of applying a health management platform combined with wearable devices to enhance stroke patients' self-management of recovery and to allow comparisons with active care intervention management. Method: This quasi-experimental study aimed at examining those participants who had sustained a stroke for the first time. A 90-day experiment was implemented with the intervention of monitoring and active care from the researchers who also interviewed the selected participants at the end of the study. A total of 26 participants were examined (14 in the experimental group and 12 in the control group). Result: The participants in the experimental group made significant progress between the pre- and post-tests. Firstly, their six-minute walking distance improved by 89.5 m ( p < 0.001). Secondly, their sit-to-stand transfers in 60 s improved 2.85 times ( p = 0.017), and their Berg balance test improved by 6.36 points ( p = 0.003). Finally, the Partners in Health scale (PIH) scores also improved. According to the data collected in the interviews, the researchers' intervention improved the patients' self-management ability. Conclusion: The short-term physical performance in the experimental group after the intervention was better than that in the control group. In clinical practice, it is suggested that continuous interaction between medical staff and patients be sustained while applying wearable devices to promote the patient's self-management ability.